Patterns of pediatric and adolescent female genital inflammation in China: an eight-year retrospective study of 49,175 patients in China - Huihui Gao; Yuchen Zhang; Yanzheng Pan; Mengjia Zhao; Ye Qi; Mingming Zhou; Symphorosa S. C. Chan; Siyi Huang; Peige Song; Kun Tang; Liying Sun; Changzheng Yuan; et al. (Frontiers Media S.A., 2023)
BackgroundGenital inflammation is one of the most frequent clinical complaints among girls, which was easily overlooked by the general public. This study aimed to investigate the patterns and epidemiological characteristics of pediatric and adolescent female genital inflammation in China.MethodsA retrospective observational study (2011 to 2018) was conducted among all female patients under the age of 0-18 years at the Department of Pediatric and Adolescent Gynecology of The Children's Hospital, Zhejiang University School of Medicine. Data were collected from the electronic medical records. The abnormal vaginal discharge of patient was collected for microbiological investigation by bacterial and fungal culture. Descriptive analysis was conducted to evaluate the genital inflammation pattern and epidemiological characteristics, including age, season, and type of infected pathogens.ResultsA total of 49,175 patients met the eligibility criteria of genital inflammation and 16,320 patients later came to the hospital for follow-up over the study period. The number of first-visit increased gradually from 3,769 in 2011 to 10,155 in 2018. The peak age of the first visit was 0-6 years old. Non-specific vulvovaginitis, lichen sclerosis, and labial adhesion were the top three genital inflammation. Among the top five potential common pathogens of vaginal infection, the prevalence of Haemophilus influenzae cases was the highest (31.42%, 203/646), followed by Streptococcus pyogenes (27.74%, 176/646), Candida albicans (14.09%, 91/646), Escherichia coli (8.51%, 55/646), and Staphylococcus aureus (6.35%, 41/636). The specific disease categories and pathogens of genital inflammation vary by age groups and season.ConclusionOur study summarizes the pattern of pediatric and adolescent female genital inflammation over an 8-year period in China, emphasizing the need for more public awareness, healthcare services and research in this field.